Monster blood II - Stine, R. L. (New York : Scholastic, 1994)
In the sequel to "Monster Blood," Evan Ross has another terrifying experience when the scary green glob he discovered the previous summer turns a classroom hamster into a huge rodent with teeth.
"An Apple paperback."
530
Accelerated Reader AR
Keywords: Supernatural -- Juvneile fiction; Horror fiction